Features of Embodiment of Communicative Strategies in I. Brodsky’s Poem “Speech Over Spilled Milk” - N. V. Chaunina (Научный диалог)
The article is devoted to one of I. Brodsky’s poems of 1967. The analysis of the poetic text is presented through the prism of communicative strategies. Theoretical and methodological basis is the works by Yu. I. Levin, O. S. Issers, I. N. Borisova et al. It is revealed that communication as an exchange of information is presented in a special way in the literary text. It is a link between the author and his potential readership. Moreover, the addressee has a different degree of manifestation: communicative intentions can be open, hidden in the subtext, and can not be expressed at all materially. The article deals with the variety of communicative relations, their dependence on “image of an addressee,” content and purpose. It is concluded that the effectiveness of interaction is directly related to the chosen communicative strategy. Three universal types of strategies are considered in more detail: regulatory, dictal, modal. The novelty of the study is due to the approach to the analysis of Brodsky’s poem in terms of the implementation of communicative intentions. On the basis of a detailed analysis of the thematic, compositional, motivic-figurative, communicative structure of the poetic text, the principles of the implementation of a particular strategy are outlined, the possible prerequisites for their use are explained, and a version of the interpretation of meanings is proposed.